Android game programming by example: harness the power of the Android SDK by building three immersive and captivating games - Horton, John (Community experience distilled, 2015)
Android gaming is a hot topic these days, but one of the few areas of technology that does not have an abundance of clear and useful documentation online. However, there is an ever-increasing demand for Android games. This book will help you get up to speed with the essentials of game development with Android. The book begins by teaching you the setup of a game development environment on a fundamental level. Moving on, the book deals with concepts such as building a home screen UI, implementing game objects, and painting the scene at a fixed resolution. Gradually, it builds up to the implementation of a flexible and advanced game engine that uses OpenGL ES 2 for fast, smooth frame rates. This is achieved by starting with a simple game and gradually increasing the complexity of the three complete games built step by step. By the end of the book, you will have successfully built three exciting games over the course of three engrossing and insightful projects.